An evaluation of motion mitigation techniques for pancreatic SBRT. Issue 1 (July 2017) - Campbell, Warren G.; Jones, Bernard L.; Schefter, Tracey; Goodman, Karyn A.; Miften, Moyed
Abstract: Background and purpose: Ablative radiation therapy can be beneficial for pancreatic cancer, and motion mitigation helps to reduce dose to nearby organs-at-risk. Here, we compared two competing methods of motion mitigation—abdominal compression and respiratory gating. Materials and methods: CBCT scans of 19 pancreatic cancer patients receiving stereotactic body radiation therapy were acquired with and without abdominal compression, and 3D target motion was reconstructed from CBCT projection images. Daily target motion without mitigation was compared against motion with compression and with simulated respiratory gating. Gating was free-breathing and based on an external surrogate. Target coverage was also evaluated for each scenario by simulating reduced target margins. Results: Without mitigation, average daily target motion in LR/AP/SI directions was 5.3, 7.3, and 13.9 mm, respectively. With abdominal compression, these values were 5.2, 5.3, and 8.5 mm, and with respiratory gating they were 3.2, 3.9, and 5.5 mm, respectively. Reductions with compression were significant in AP/SI directions, while reductions with gating were significant in all directions. Respiratory gating also demonstrated better coverage in the reduced margins scenario. Conclusion: Respiratory gating is the most effective strategy for reducing motion in pancreatic SBRT, and may allow for dose escalation through a reduction in target margin.